Book review: Clydesdale, Greg. 2021: Reducing Inter-generational Ethnic Poverty: Economics, Psychology and Culture. (January 2023) - Ma, Mengxing
Clydesdale, Greg. 2021: Reducing Inter-generational Ethnic Poverty: Economics, Psychology and Culture (1st Edition). London: Routledge. vi + 121 pp. £120.00 (paperback), £33.29 eBook. ISBN 9780367616298 paper, 9781003105770 eBook. 10.4324/9781003105770.